Increasing abdominal circumference in children – does it require diagnosis? Assessment of the incidence of Wilms tumor among children at the University Children’s Hospital in Lublin - Miazga, Małgorzata; Ostojska, Magdalena; Stręk, Wojciech; Maślana, Marianna; Bogoń, Aleksandra; Woźniak, Magdalena Maria (Quality in Sport, 2024)
Introduction and purpose: Wilms tumor, also known as nephroblastoma, is the most prevalent malignant tumor of the kidney in the pediatric population. 90% of them are diagnosed in children before the age of 6. This tumor is more common in girls, and usually occurs unilaterally. The purpose of the study is to analyse and present the incidence of the patients with Wilms tumor in University Children’s Hospital in Lublin in comparison to other studies published on PubMed. Material and methods: The study included 34 patients with the Wilms tumor in the past medical history. They were selected among patients who had a computed tomography (CT) scan in the Department of Pediatric Radiology between November 2012 and October 2021. Results: The average diagnostic age of Wilms tumor patients was 3 years and 9 months. The unilateral occurrence of the tumor was more common, also, the presence of a tumor in the left kidney was more frequent than in the right one. Metastases were mainly located in the lungs and liver. The less common sites of metastasis were pleural recesses and paraaortic lymph nodes. Treatment was mostly based on nephrectomy and chemotherapy, and less frequently, on radiotherapy. In the majority of patients, treatment resulted in regression of cancer lesions. Only a few recurrences of the disease were reported. Conclusions: Successful treatment protocols for Wilms tumor (pre-operative chemotherapy and surgery) ensure a high survival rate. It is important to monitor the patient after treatment due to the risk of recurrence. During diagnostics, chest and abdominal CT should be considered because of the high incidence rate of lung and liver metastases.